Developmental changes in the spelling of derivational suffixes by typically developing Greek children: effects of transparency, lexicality, letter length and frequency. Issue 1 (2nd January 2019) - Tsesmeli, Styliani N.
ABSTRACT: The study aimed to investigate developmental changes in the spelling performance of derivational suffixes by 188 Greek school children (ages: 7–14 ½) of typical development, along with effects of transparency, lexicality, length and frequency. Children were evaluated preliminary by a standardised spelling task followed by three experimental spelling tasks of derivations constructed for the study. In particular, the first task entailed 88 related pairs of derivations and pseudo-derivations matched in terms of phonological transparency of their suffixes (transparent vs. opaque). The second task entailed 40 derivationally related words classified in terms of suffix length (one- vs. two- vs. three-syllables), while the third task comprised of 20 related pairs of derivations equally allocated into high and low frequent items in terms of suffixation. Results showed that developmental differences of the derivational acquisition were significant in the first two years of schooling. Accordingly, the effects of phonological transparency, length and frequency of derivational suffixes were most prominent in the first years of schooling than in the later years. These results are compatible with the experimental literature and have important implications for designing adequate assessments of orthography for typically developing children or those with spelling disabilities or dyslexia.